ANALISIS ASESMEN KEBUTUHAN DALAM PENYUSUNAN RENCANA KERJA SEKOLAH (RKS) di SMP NEGERI 3 MARTAPURA - Rahman, Arif; Yuliansyah; Sulistiyana; Suhaimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of needs assessment in the preparation of the School Work Plan (RKS) at SMP Negeri 3 Martapura. Needs assessment serves as a fundamental basis for data-driven planning and school quality improvement. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis of the School Work Plan (RKS), School Budget Plan (RKAS), School Self-Evaluation, and Education Report data. Informants included the principal, vice principal, RKS drafting team, teachers, and the school committee. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña involving data reduction, data display, and conclusion drawing simultaneously. The findings reveal that needs assessment was conducted systematically through the collection of actual school data, gap analysis between current and expected conditions, and priority setting based on urgency, impact on learning quality, alignment with school vision and mission, and budget availability. The process was participatory, involving teachers, the school committee, and student representatives. The results of the needs assessment were integrated into the RKS in the form of priority programs, performance indicators, achievement targets, and resource allocation. This study proposes a conceptual model of needs assessment characterized by data-based, participatory, and strategic-rational dimensions.